What Works 2? Graduates as Advisors for Transition and Students’ Success - Millard, Luke; Janjua, Rohzeena (Frontiers in Education, 2020)
Will there ever be a University that provides sufficient staffing resource to provide the perfect academic advising and tutoring service to all students? There may also be the small matter of a debate as to what that perfect service may offer. This article will discuss one University’s approach that sought to makes effective use of staffing resource, offers significant development opportunities for those staff and ensure relevance and connectivity between students and their staff. The model that was designed, and is now embedded, focused on the creation of an integrated system of Student Success Advisers (SSA). These roles were filled by students who had just completed their degree in the faculty in which they are then employed. This new staffing resource targets a specific aspect of support and advising for students that focuses upon student transition and the first year experience. The SSAs are viewed by students as relevant and relatable providing an approachable interface between students and staff, and evidence suggests that it works. The roles were created through the University’s participation in the Higher Education Academy’s What Works Student Retention and Success programme (2012-2016) and now sees 17 SSAs employed across the University. This article will consider the creation of the role and its fit to the the university; offer clarity around role objectives and provide insights from GSSAs on impact of the role. It will then detail how the role grew and became embedded across the university, explaining the integration with the university’s wider student support system to engage students through their transition and first year experience.